Υπολογιστική ανάλυση λειτουργικών δικτύων διασυνδεσιμότητας του ανθρώπινου εγκεφάλου με βάση τη θεωρία της Granger αιτιότητας και των Κατευθυνόμενων Συναρτήσεων Μεταφοράς (Directed Transfer Function) - Οφλίδη, Γενοβέφα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών. Τομέας Μηχανικής, 2016)
The purpose of this thesis is to study and analyze neurophysiological data with the use of Granger Causality and Directed Transfer Functions (DTF). We give a brief review of the brain physiology and an overview of the methods used in time-frequency domain analysis. We also present the stochastic processes theory and focus on spectral analysis of multivariate autoregressive models (MVAR). Finally, we introduced the theory of G-causality and DTF and we apply their methods to simulated signals, with known patterns of connectivity.